Cimanuk Traffic Noise Analysis, Garut Regency - Zhafirah, Athaya; Siddiq, Mochammad Yoghi Zafar (Jurnal Teknik Sipil, 2023)
Cimanuk Road, Garut, is a road segment located in the middle of the city and is included in the trade area. Cimanuk Road has relatively high vehicle traffic activity, affecting traffic noise levels. Traffic noise can interfere with the activities of residents around Cimanuk Road, such as offices, hospitals, schools, and settlements, if the noise exceeds the specified quality standard. Traffic noise continuously occurs and, in the long term, will impact public health. Based on this, this research aims to calculate traffic volume and noise level and create a traffic noise model. The method used is direct data collection in the field and to analyze traffic noise modeling using multiple linear regression analysis with the help of SPSS version 28.0. The analysis results show that the highest noise value during holidays at point 1 and point 2 is 83,3 dB and 79,5 dB, respectively. While on weekdays, the highest noise is at point 1 at 81,3 dB and point 2 at 81,2 dB. The noise that occurs has exceeded the threshold, which is 70 dB for trade and service locations. The vehicle with the most influence on traffic noise is a motorcycle, with 86,5%.